Subglacial Water Flow Over an Antarctic Palaeo-Ice Stream Bed - Hogan, KA; Arnold, NS; Larter, RD; Kirkham, JD; Noormets, R; Ó Cofaigh, C; Golledge, NR; Dowdeswell, JA (American Geophysical Union (AGU), 2022)
Abstract The subglacial hydrological system exerts a critical control on the dynamic behavior of the overlying ice because its configuration affects the degree of basal lubrication between the ice and the bed. Yet, this component of the glaciological system is notoriously hard to access and observe, particularly over timescales longer than the satellite era. In Antarctica, abundant evidence for past subglacial water flow over former ice‐sheet beds exists around the peripheries of the ice sheet including networks of huge channels carved into bedrock (now submarine) on the Pacific margin of West Antarctica. Here, we combine detailed bathymetric investigations of a channel system in Marguerite Trough, a major palaeo‐ice stream bed, with numerical hydrological modeling to explore subglacial water accumulation, routing and potential for erosion over decadal‐centennial timescales. Detailed channel morphologies from remotely operated vehicle surveys indicate multiple stages of localized incision, and the occurrence of potholes, some gigantic in scale, suggests incision by turbulent water carrying a significant bedload. Further, the modeling indicates that subglacial water is available during deglaciation and was likely released in episodic drainage events, from subglacial lakes, varying in magnitude over time. Our observations support previous assertions that these huge bedrock channel systems were incised over multiple glacial cycles through episodic subglacial lake drainage events; however, here we present a viable pattern for subglacial drainage at times when the ice sheet existed over the continental shelf and was capable of continuing to erode the bedrock substrate.